PENGETAHUAN KELUARGA TENTANG FAKTOR PENYEBAB DAN PENCEGAHAN DIABETES MELITUS - Dina Alviyanti; Amelia Dini Anggraini Silalahi (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
Diabetes (DM) or also known as diabetes mellitus is a chronic metabolic disorder caused by the insulin hormone in the body that cannot regulate blood sugar levels effectively, causing an increase in blood sugar levels. This study aims to increase public awareness about the causes and impacts of diabetes. The research method uses a